Purification of archetypal soybean root suberin mostly comprising alka(e)noic acids using an ionic liquid catalyst - Escórcio, Rita; Sandhu, Armaan K.; Bento, Artur; Tomé, Ana S.; Moreira, Carlos J. S.; Brözel, Volker S.; Silva Pereira, Cristina (Frontiers in Chemistry, 2023)
Soybean (Glycine max) is an increasingly relevant crop due to its economic importance and also a model plant for the study of root symbiotic associations with nodule forming rhizobia. Plant polyesters mediate plant-microbe interactions with both pathogenic and beneficial microbes; suberin has been hypothesized to play a key role during the early steps of rhizobia attachment to the root. The downside is that suberin chemistry in soybean root is still scarcely studied. This study addresses this outstanding question by reporting a straightforward workflow for a speedy purification of suberin from soybean root and for its subsequent detailed chemical analysis. To purify suberin, cholinium hexanoate (an ionic liquid) was used as the catalyst. The ensuing suberin is highly esterified as observed by a precise NMR quantification of each ester type, discriminating between primary and acylglycerol esters. Moreover, the composing hydrolysable monomers detected through GC-MS revealed that hexadecanoic acid is the most abundant monomer, similar to that reported before by others. Overall, this study highlights the adequacy of the ionic liquid catalyst for the isolation of suberin from soybean roots, where the polymer natural abundance is low, and builds new knowledge on the specificities of its chemistry; essential to better understand the biological roles of suberin in roots.